The decline of sterling : managing the retreat of an international currency, 1945-1992 - Schenk, Catherine R. (Catherine Ruth), 1964- (Cambridge : Cambridge University Press, 2010)
The demise of sterling as an international currency was widely predicted after 1945, but the process took thirty years to complete. Why was this demise so prolonged? Traditional explanations emphasize British efforts to prolong sterling's role because it increased the capacity to borrow, enhanced prestige, or supported London as a centre for international finance. This book challenges this view by arguing that sterling's international role was prolonged by the weakness of the international monetary system and by collective global interest in its continuation. Using the archives of Britain's partners in Europe, the USA and the Commonwealth, Catherine Schenk shows how the UK was able to convince other governments that sterling's international role was critical for the stability of the international economy and thereby attract considerable support to manage its retreat. This revised view has important implications for current debates over the future of the US dollar as an international currency.
Introduction -- Reconstructing the International Monetary System 1945-59 -- The post-war international monetary system 1945-50 -- Return to convertibility 1950-59 -- Accelerating the Retreat: Sterling in the 1960s -- Sterling and European integration -- The sterling devaluation 1967: relations with the USA and the IMF -- Sterling and the City -- Multilateral negotiations: sterling and the reform of the international monetary system -- The sterling agreements of 1968 -- Sterling's Final Retreat 1970-1992 -- Sterling and the end of Bretton Woods -- Years of crisis 1973-79 -- The aftermath 1980-1992 -- Summary and conclusions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: elektronické knihy; electronic books; Pound, British -- History -- 20th century; Monetary policy -- Great Britain -- History -- 20th century; International economic relations -- History -- 20th century